Extended post-exercise hyperthermia in athletes with a spinal cord injury - Maloney, P. L.; Pumpa, K. L.; Miller, J.; Thompson, K. G.; Jay, O. (Journal of Science and Medicine in Sport, 2021)
Objectives: Determine the extent and underlying causes of post-exercise hyperthermia in athletes with a spinal cord injury following exercise. Design: Observational. Methods: Thirty-one males (8 with tetraplegia [TP; C5-C8], 7 with high paraplegia [HP; T1-T5], 8 with low paraplegia [LP; T6-L1] and 8 able-bodied [AB]), recovered in 35 °C/50%RH for 45 min after 30-min of exercise at a metabolic heat production (Hprod) of 4.0 W/kg (AB vs TP) or 6.0 W/kg (AB vs HP vs LP). Esophageal (Tes), gastrointestinal (Tgi) and skin temperatures, Hprod, local sweat rate (LSR) and mean arterial pressure were measured. Results: TP maintained a higher Tes (38.05 °C [95% CI: 37.83 °C, 38.28 °C], AB: 36.77 °C [36.56 °C, 36.98 °C], p < 0.001) and Tgi (TP: 38.36 °C [38.15 °C, 38.58 °C], AB: 37.26 °C [37.04 °C, 37.47 °C], p < 0.001), with peak values observed 45 min post-exercise. Core temperatures all declined in HP, LP and AB, but HP maintained a higher Tes than AB (p = 0.030), and higher Tgi than LP and AB (p = 0.019). No differences in post-exercise Hprod were observed between TP and AB (p = 0.264), or HP, LP and AB (p = 0.124). Evaporative heat loss was estimated to be zero in TP, while back LSR was greater in HP than LP (p = 0.009). Minimal dry heat loss occurred in SCI groups (TP: 9 W/m2 [6, 12], HP: 4 W/m2 [1, 6], LP: 2 W/m2 [0, 5]). Conclusions: Substantial post-exercise hyperthermia is evident in TP (~1.4 °C hotter than AB after 45 min of post-exercise recovery) due to minimal evaporation. HP have delayed post-exercise thermoregulatory recovery whereas LP respond similarly to AB.